Regime changes in monetary policy and the Expectation Hypothesis of the term structure in Turkey - Özdemir, K. Azim; Özel, Özgür (Journal of Business Economics and Management, 2012)
In this study we test the long-run validity of the Expectation Hypothesis of the Term Structure (EHTS) in Turkey by using monthly interest rate series from 2003m1 to 2010m1. The data set is obtained from the bonds and bills market for the government securities in the Istanbul Stock Exchange (ISE). Several results arise from our empirical analysis. First, we find strong evidence that there are stationary combinations of the long and short rates during the sample period. Secondly, when we restrict the cointegrating vectors to be the spread vectors between short and long rates we are not able to reject the restriction if the dynamic specifications of the systems include 2 lags of the interest rates. This result, however, is not robust to the lag length of 4 and 6 if the systems include interest rates with maturities longer than 6 months. Finally, the formal stability test results suggest that the regime change from the implicit to the full-fledged inflation targeting (IT) has no significant effect on the relationship among the interest rates on the short end of the term structure while the structural instability found in the relationship between the short rates and the long rates with maturity longer than 6 months might indicate the effect of the regime shift on this relationship. These results are in line with the conclusions of the literature that argues the EHTS to hold for the short end of the term structure when the focus of the monetary policy is to stabilize the short-term interest rates.